Application of material flow cost accounting to achieve environmental sustainability in small-scale soybean oil production in South Africa - Ayotola Joel; Mishelle Doorasamy; Wilfred Akinola (Economics, Management and Sustainability)
Purpose: This study investigates the effectiveness of Material Flow Cost Accounting (MFCA) as a tool for enhancing resource efficiency and environmental sustainability in small-scale soybean oil production in South Africa. The main objective is to analyze the impact of MFCA on waste reduction and economic performance within the production process.